British Association for Sexual Health and HIV Scottish Investigation 2010–2011: reasons for non-attendance in individuals lost to follow-up for HIV care for more than 12 months in Scotland. (June 2013) - Cullen, B L; Codere, G; Wallace, L A; Baguley, S; Clutterbuck, DJ
Summary: As of 31 March 2011, 6696 HIV diagnoses had ever been reported in Scotland; of these, 1791 individuals had died, 3339 were attending specialist services, but the remainder had defaulted from specialist care; an investigation into their reasons for non-attendance, and the efforts of services to re-engage, was undertaken by British Association for Sexual Health and HIV Scottish branch using a web-based survey questionnaire. Twelve of the 13 Scottish HIV services returned information for 424 of 579 eligible cases; 112 of these 424 individuals were identified as genuine non-attendees. Findings indicate that the epidemiology of these non-attendees is similar to that of the whole Scottish HIV cohort. Three-quarters of individuals failed to attend a booked appointment following their last known attendance and very few attempts to contact non-attending individuals were successful. This survey has refocused attention on those lost to follow-up, while quality of the national data-set has improved, providing a clearer epidemiological picture of people living with HIV in Scotland.